CENTRAL CONGENITAL HYPOTHYROIDISM IN AN INFANT OF A MOTHER WITH GRAVES’ DISEASE - Halim, Halimah Abdul; Khuzaini, Aliyyah Mohammad (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION We report a case of central congenital hypothyroidism in a preterm baby born to a mother with hyperthyroidism. CASE The mother has been on treatment for hyperthyroidism since 2018. She developed thyrotoxicosis at 30 weeks pregnancy requiring Lugol’s iodine, carbimazole and propranolol. She subsequently developed pre-eclampsia and went into labour. Her Thyroid Stimulating Hormone (TSH) receptor antibody levels were high, while anti-peroxidase and anti-thyroglobulin antibodies were negative. The child was born at 31 weeks gestation. Initially the cord TSH level was 0.021 mIU/L. Subsequently, regular thyroid function tests continued to show very low TSH with normal T4. At one month of life, the T4 levels were low with persistent very low TSH and therefore the child was started on L-thyroxine. TSH receptor antibodies were positive. He was noted to have constipation and an umbilical hernia during this review. The diagnosis of central congenital hypothyroidism (CCH) was made, and the child was started on L-thyroxine. After initiation of therapy, T4 levels have normalised. CCH is a rare condition with prevalence of 1 in 180 000 children. The risk is significantly increased in infants born to mothers with Grave’s disease. In Grave’s disease, patients may have TSH-blocking antibodies that bind to TSH receptors but do not initiate intracellular signaling, resulting in hypothyroidism. These antibodies can freely cross the placental, especially during the second and third trimester. Fetal thyroid matures functionally at around 25 weeks of gestation and because of this the hypothalamic-pituitary-thyroid axis can be affected in utero or postnatally. CONCLUSION This case highlights the importance of monitoring T4 and TSH levels in infants born to women with Grave’s disease.